Terrorist offenses, penalty and compliance separation of powers: the case "De Juana Chaos" (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The media has paid attention every day during the past months, increasing the social tension, to these events that are now analysed from a criminal law point ofview: political testimonies against the order to release him from prison, press articlesin GARA, different reports from the Public Prosecutor Office, juditial reactions from the initial dismissal to the conviction Judgment issued by the National Courtand to the condemn of the Supreme Court and its change of mind-, ending with the controversial diminished execution of the punishment. This article carries out a critical anylisis of the different resolutions from the juridical point of view of the constitutional guarantees, without taking into account any political determining factor.
Keywords: terrorism; threats; membership and collaboration with a terrorist group; hunger strike and punishment execution